Molecular identification of butterfly larval host plants using chloroplast matk and RBCL genes (Bangladesh Journal of Botany, 2026)
This study used DNA barcoding with matK and rbcL genes to identify thirteen butterfly larval host (BLH) plants. BLAST analysis of matK and rbcL gene sequences confirmed 99.04-100% similarity with global records. The matK gene showed significantly more variable (624) and parsimony-informative sites (521), making it suitable for resolving relationships at lower taxonomic levels. In contrast, rbcL had more conserved sites (351), highlighting its effectiveness at higher taxonomic levels. These differences underscore the complementary roles of matK and rbcL in phylogenetic studies. Phylogenetic trees were constructed with matK and rbcL gene sequences which showed consistent topologies and evolutionary relationships. The variable matK gene proved effective for species-level resolution, while the conserved rbcL gene offered stronger support at broader taxonomic classification. Robust bootstrap values (98-100) confirmed the reliability of both markers. Their complementary features make them valuable tools for DNA barcoding and understanding the evolutionary history of BLH plant species.Bangladesh J. Bot. 55(1): 37-43, 2026 (March)